Analysis and optimization of load matching in photovoltaic systems for zero energy buildings in different climate zones of China. (20th November 2019) - Liu, Changping; Xu, Wei; Li, Angui; Sun, Deyu; Huo, Huimin
Abstract: Load matching is an inevitable problem that restricts the development of photovoltaic (PV) system used in buildings. The objective of this paper is to solve this problem by conducting a load matching assessment and optimization of PV system in different climate zones of China. The influences of the tilt angle, orientation, PV plot ratio and building height on the achievement of zero energy buildings (ZEBs) were evaluated. The PV potentials of roofs and facades were analyzed and optimized based on self-sufficiency and self-consumption. Net load variance and the maximum electricity import were employed as indices to evaluate the performance of PV systems in different climate zones of China. The results of the load matching assessment show that electricity generations from roof PV systems in low-rise buildings can meet most of the energy demand (at least 70%) in all climate zones of China. East and west facades of mid-rise buildings have an advantage over south façades in Kunming and Guangzhou in terms of load matching. It is necessary to combine roofs, south, east and west facades to meet the ZEBs requirement of for high-rise building. When the heating/cooling demand is dominant, the tilt angle should be higher/lower than the latitude of the specific location. This research will be helpful in designing building PV systems in different climate zones of China. Graphical abstract: Load matching analysis is helpful in designing building PV system in different climate zones of China. The results show that east and west facades of mid-rise buildings have an advantage over south façade in Kunming and Guangzhou. It is necessary to combine roof, south, east and west facades to meet the requirement of ZEBs for high-rise building.Image 1 Highlights: Load matching with PV system were analyzed for zero energy buildings. PV potential were investigated based on self-sufficiency and self-consumption. The optimal combinations of PV system were obtained in different climate zones. East and west facades have advantages over south façade in Kunming and Guangzhou.